Antisense oligonucleotide exon-skipping as a therapeutic approach for Mucolipidosis type II a/b: in vitro and in vivo studies - Matos, Liliana (2021)
Mucolipidosis type II alpha/beta (ML II) is one of the most severe Lysosomal Storage Disorders and is caused by the deficiency of the enzyme GlcNAc-1-phosphotransferase. This enzyme is responsible for the addition of the mannose 6-phosphate marker to lysosomal enzymes, which allow their targeting to lysosomes. Of the several mutations that occur in ML II, the deletion of 2 nucleotides from GNPTAB exon19 (c.3503_3504del) is the most frequent, making it a good target for a specific mutation therapy as there is no therapy for this disease. In this study, we explored the possibility of an innovative therapeutic strategy based on the use of antisense oligonucleotides (AOs) for ML II. In a previous in vitro study in ML II patient fibroblasts, AOs were used to promote the exon 19 skipping from the GNPTAB pre-mRNA, resulting successfully in the production of an in-frame mRNA. Currently, our objective is to evaluate the therapeutic potential of this approach, both in vitro in C57BL/6 fibroblasts and in vivo in C57BL/6 mice. For this, 18 animals were used, divided into 6 groups: groups 1 and 4 were injected with saline solution, groups 2 and 5 with AO at 25 mg/kg and groups 3 and 6 with AO at 50 mg/kg. All animals were injected by intraperitoneal route and were sacrificed after 4 or 7 days post-treatment. At the end of the experiment, the organs were collected and frozen at -80ºC, for later RNA extraction, cDNA synthesis and RT-PCR. After results analysis, the exon 19 skipping was not observed using any of the tested doses or incubation periods. So, we can theorize that the doses administered were not sufficient to achieve a response or the AO might have had a high clearance rate. As for the in vitro experience, the C57BL/6 fibroblasts were seeded in 6-well plates and subsequently transfected with concentrations of AO ranging from 10nM to 600nM. After 24/48h of incubation, cells were collected and cDNA analysis revealed a full length transcript but also another one of lower molecular weight compatible with exon-skipping. These are preliminary data, so in the near future more experiments will be done.